1988
DOI: 10.1002/art.1780311216
|View full text |Cite
|
Sign up to set email alerts
|

Hla—dr antigens and anticardiolipin antibodies in northern italian systemic lupus erythematosus patients

Abstract: Eighty systemic lupus erythematosus (SLE) patients attending 3 clinical centers were evaluated immunologically and immunogenetically. No HLA class I1 antigens were found to be significantly associated with SLE in these patients. A highly significant (P = 6.17 X lo-') association was observed between anticardiolipin antibodies and DR7. A lesser association (P < 0.025) was also observed between DR2 and/or DR3 and anti-Ro (SS-A) antibodies. No relationship was found between any DR antigen and anti-Sm/RNP, antidou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
31
0

Year Published

1989
1989
2011
2011

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 80 publications
(35 citation statements)
references
References 14 publications
2
31
0
Order By: Relevance
“…The data confirmed in a population from Spain [25] and Canada [7]. Studies of HLA alleles in patients with conventianal aCL showed increased frequencies of HLA DR4 [26] or DR7 [25,27] in SLE population. DR7 was also increased in Mexican patients with aCL [28].…”
Section: Genes Associated With Antiphospholipid Syndromesupporting
confidence: 69%
“…The data confirmed in a population from Spain [25] and Canada [7]. Studies of HLA alleles in patients with conventianal aCL showed increased frequencies of HLA DR4 [26] or DR7 [25,27] in SLE population. DR7 was also increased in Mexican patients with aCL [28].…”
Section: Genes Associated With Antiphospholipid Syndromesupporting
confidence: 69%
“…A number of diseases are linked to these specificities, some of which also have clinical and pathogenetic features relevant to CSS. Among autoimmune conditions, RA is associated with HLA-DRB1*04 (35), and HLA-DRB7 has been found to correlate with the occurrence of anticardiolipin antibodies in systemic lupus erythematosus (36). Some vasculitides are also associated with such HLA alleles: giant cell arteritis is significantly associated with HLA-DRB1*04 (14).…”
Section: Discussionmentioning
confidence: 99%
“…Most other published reports that have documented the association of HLA genes with aPL expression involved unrelated patients. These studies suggest an increased association of aPL with HLA-DR4 (4,5,7-9), HLA-DR7 (6,8), DRw53 (7-9), and C4A or C4B null alleles (11). The ethnic background of the population being studied appears to be important.…”
Section: Familial Antiphospholipid Syndrome and Hla-drb Gene Associatmentioning
confidence: 99%
“…The ethnic background of the population being studied appears to be important. For example, Savi et a1 (6) found that HLA-DR7 was increased in a group of Italian patients, while HLA-DR4 was predominant in a group of English patients (3, and C4 null alleles were more commonly encountered in a group of black patients (11).…”
Section: Familial Antiphospholipid Syndrome and Hla-drb Gene Associatmentioning
confidence: 99%